Promotion and Brand Image as a Marketing Management Modality - NGURAH, Ida Bagus (Journal of Entrepreneurial and Business Diversity, 2025)
Purpose:A product is an inanimate object that a potential force must drive, and all force is exerted, including the psychological tension that is raised. The product must be able to appear in the mind or psychology of the consumer as the first step of attribution to the consumer so that the product owns various modalities. This research leads to the elaboration of how to promote and create brand image as a modality in marketing management.Methodology:Documentation methods in various research results are expected to provide provisional answers or hypotheses related to promotion and Brand Image can affect consumers' desire to consume a product.Findings:One of the effects of promotion is how to administer the product, the person or person, the price or price, place or place, and the process that will all be toned in one piece, namely promotion.Implication:The creation of a Brand Image must touch the psychology of consumers in a broader measure of how the product is attached not only as a product to be consumed but as a product that can image oneself or consumers.